An ultraviolet based methyl mercaptan system for halitosis using an optical fibre sensor - Suzalina, Kamaruddin (2020)
Halitosis is a foul smells from the mouth, mainly originate from the putrefactive bacteria that produce volatile sulphur compounds (VSCs), predominantly methyl mercaptan (CH3SH). It has become public concerned which needs well structured procedure for detection purpose. However, current systems or methods failed to identify and distinguish main components of VSCs, sensitive to the environment and provide immeasurable results. Optical detection system is found to be more reliable than gas chromatograph, portable sulphide monitors, electronic noses and chemical or enzymatic tests. Main purpose of this study is to develop an ultraviolet (UV) based methyl mercaptan system using optical fibre sensor (OFS) to detect halitosis. The proposed system is utilised to obtain the absorption cross section spectra of CH3SH, the main component of VSCs for the analyses and wavelength spectral determination. To validate the proposed system, cross sensitivity evaluation with breathing gases and calculation of CH3SH gas concentration is performed. Methodology of the study is based on the absorption spectroscopy method. The working principle of the proposed system involved propagation of UV light signal from its source through the input fibre and then modulated by measurand in the modulation zone before it is sensed by spectrometer as the detector through the output fibre. The modulation zone is where the open path technique will take place. Each gases has their unique characteristic which corresponds to their identification and can be determined using this detection system as the measurand. By manipulating the Beer Lambert Law equation, the datasets of absorption cross section, σ for CH3SH was obtained and plotted against wavelength. The result was found to be highly correlated (coefficient = 0.99) with theoretical datasets from the MPI Mainz UV-VIS database. σ for O2 and CO2 were obtained for system validation purposes. Cross sensitivity evaluation of CH3SH which was carried out with breathing gases O2, CO2 and water (H2O) proved that interference was not an issue for UV wavelength region of 200 to 270 nm. And, the calculated CH3SH gas concentration is 97.46 ppm almost reach the 100 ppm that was stated by manufacturer. Finally, the proposed system is capable of detecting CH3SH in the UV-C region, with the best potential band of 200 to 210 nm where the excellent peak located. The UV based detection system with OFS which was constructed with available manufactured components is able to detect halitosis, distinguished different gases, not sensitive to interference and can produce measurable results for routine clinical usage in the dental field.